2004
DOI: 10.1194/jlr.m400074-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

High dietary intake of phytosterol esters decreases carotenoids and increases plasma plant sterol levels with no additional cholesterol lowering

Abstract: The objective of this study was to measure the effects on serum lipids and plasma phytosterols of 6.6 g/day phytosterols from three foods (bread, breakfast cereal, and spread) consumed for 12 weeks compared with a diet that was not enriched with phytosterols. Thirty-five subjects undertook a nonrandomized, single-blind study consisting of a 2 week baseline period, 6 weeks on high-phytosterol intake, 6 weeks on high-phytosterol intake plus increased fruit and vegetable intake, and a final 2 week washout period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 27 publications
4
32
0
Order By: Relevance
“…Similar changes were reported in rats treated with high doses of stanol ester for 13 weeks (156). However, when the levels of these vitamins were adjusted to the lowered LDL-C concentrations, the reduction was not significant for vitamin E, D and K (9, 41, 106), while plasma levels of α-, β -carotene and lycopene remained low (9,41,153,157). The effects of plant sterols on fat soluble vitamins can be overcome by maintaining adequate daily intake of fruits and vegetables (1,9,158).…”
Section: Short and Long Term Safety And Toxicity Of Sterols And Stanolssupporting
confidence: 69%
See 1 more Smart Citation
“…Similar changes were reported in rats treated with high doses of stanol ester for 13 weeks (156). However, when the levels of these vitamins were adjusted to the lowered LDL-C concentrations, the reduction was not significant for vitamin E, D and K (9, 41, 106), while plasma levels of α-, β -carotene and lycopene remained low (9,41,153,157). The effects of plant sterols on fat soluble vitamins can be overcome by maintaining adequate daily intake of fruits and vegetables (1,9,158).…”
Section: Short and Long Term Safety And Toxicity Of Sterols And Stanolssupporting
confidence: 69%
“…Few clinical trials have shown that the use of high doses of plant sterols/ stanols was associated with a modest reduction in levels of carotenoids, fat-soluble vitamins and antioxidants (40,94,(153)(154)(155). Similar changes were reported in rats treated with high doses of stanol ester for 13 weeks (156).…”
Section: Short and Long Term Safety And Toxicity Of Sterols And Stanolsmentioning
confidence: 77%
“…In a crossover trial supplementation with 1.8 g per day of PS to 63 healthy individuals elevated plasma campesterol plus sitosterol concentrations from 9.0 to 16.6 mmol l À1 and 4.4 to 6.0 mmol l À1 (Mussner et al, 2002). Clifton et al (2004) showed that supplementation with a larger dose of 6.6 g per day in 35 mildly hypercholesterolemic subjects increased campesterol and sitosterol concentrations to a similar extent (7.8-15.8 and 8.0-11.4 mmol l À1 , respectively). No studies thus far, however, have considered the extent to which PS intake elevates concentrations of plasma campesterol and sitosterol as a function of natural circulating levels as was done presently.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of the individual sterols in serum were quantified using a modified method as described previously by Wolthers et al (1991). The method was based on saponification followed by extraction, silylation and analysis by gas chromatography with flame ionization detection (GC-FID) using an internal standard for calibration as described previously (Clifton et al, 2004). All analyses were performed on an Agilent 6890N GC equipped with an on-column injector (Agilent Technologies, Sydney, Australia).…”
mentioning
confidence: 99%